I-κB kinase-ε deficiency improves doxorubicin-induced dilated cardiomyopathy by inhibiting the NF-κB pathway - Liu, Yafeng; Xu, Yueyue; Yao, Yiwei; Cao, Yide; Chen, Ganyi; Cai, Yuchen; Chen, Wen; Chen, Xin; Qiu, Zhibing (Frontiers in Physiology, 2022)
Dilated cardiomyopathy (DCM) can lead to heart expansion and severe heart failure, but its specific pathogenesis is still elusive. In many cardiovascular diseases, I-κB kinase-ε (IKKε) has been recognized as a pro-inflammatory molecule. In this study, wild-type mice (WT, n=14) and IKKε knockout mice (IKKε-KO, n=14) were intraperitoneally injected with a cumulative dose of 25 mg/kg by Dox or Saline via five times in 30 days. Finally, the experimental mice were divided into WT+Saline group、WT+DOX group、IKKε-KO+Saline group and IKKε-KO+Dox group. Echocardiography was performed to assess cardiac structure and function. Moreover, the mechanism was validated by immunohistochemistry and western blotting. Our results demonstrated that compared to WT+Dox mice, IKKε-KO+Dox mice exhibited attenuation of dilated cardiomyopathy-related morphological changes and alleviation of heart failure. Additionally, compared to the WT mice after Dox-injected, the expression of fibrosis and proinflammatory were decreased in IKKε-KO mice, and the expression of cardiac gap junction proteins were much higher in IKKε-KO mice. Further testing found that pyroptosis and apoptosis in myocardium were also ameliorated in IKKε-KO mice compared to WT mice after Dox was injected. Mechanistically, our results showed that deficiency of IKKε might inhibit the phosphorylation of IκBα, p65, RelB ,and p100 in mouse heart tissues after Dox stimulation. In summary, our research suggests that IKKε might play an essential role in the development of Dox-induced dilated cardiomyopathy and maybe a potential target for the treatment of dilated cardiomyopathy in the future.